Modeling discontinuous rock mass based on smoothed finite element method. (October 2016) - Zhang, Wei; Dai, Beibing; Liu, Zhen; Zhou, Cuiying
Abstract: This paper aims at developing a method for modeling rock mass with preexisting multiple discontinuities within the framework of the smoothed finite element method (SFEM). The discontinuity is simulated by an interface element with zero thickness, the stiffness matrix of which are derived explicitly based on the SFEM. An elastic damage constitutive relation with residual strength is introduced in order to describe the nonlinear mechanical behavior of the discontinuities. The computation codes of the present method were developed. The present method has been verified to be a sound approach for modeling discontinuous rock mass, inheriting the advantages of the SFEM.